Paradigma Pendidikan Katolik: Kajian Komparasi atas Paradigma Pendidikan Nilai dan Karakter di Indonesia - Yusuf Siswantara (Sekolah Tinggi Agama Katolik Negeri Pontianak, 2022)
Education is colored by a tug-of-war between general education and specialist education where one eye is often directed towards general education. This condition occurs in academic institutions. But in fact, general education delivers students to real humans, namely the development of the overall potential of humans as human beings. Religious Education, one of the general education courses, undoubtedly needs to form a pedagogical paradigm. In this context, the grand theory of education is very important in determining the paradigm of religious education (specifically) or MKDU (in general). Through a qualitative approach with the comparative analysis method, this study examines major theories in education to find their implementation in Catholic religious education. The question is which paradigm or theory contributes paradigmatically to national education in Indonesia? This study uses a qualitative approach. Using the library research method, this study conducted a critical analysis and found that theoretically, the three models described by Robert R. Newton are strong in their strengths and weaknesses. Therefore, in practical terms, the mixed model is a wise step in implementing Catholic Religious education to present faith in the heart and action.